Perspektif Transportasi Maritim Global dan Transpotasi Maritim Indonesia dalam Menghadapi Kenormalan Baru - Hari Sucahyowati; Andi Hendrawan (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2022)
A large-scale pandemic and in a situation of uncertainty faced by the community and all sectors of life activities make it one of the difficulties for maritime business actors to overcome and respond to the new normal. This article presents data from the results of a literature search that describes the declining trend of global and national maritime transportation. The method used in this article is a literature study technique, which is a data collection technique carried out by searching for data from various sources of information as data sources, then presented as a perspective that describes the conditions of maritime transportation. During the pandemic, there was a downward trend, the real impact of the Coronavirus Covid-19 pandemic on the maritime industry in Indonesia was also quite large, as seen from the decline in Container Traffic at Indonesian ports, which decreased by 738,181 TEU. Changes in the way of working become a necessity that cannot be avoided and must be carried out by the organization in achieving its goals, the organization must make many adjustments.